Risk Preferences Around the World - Rieger, Marc Oliver; Wang, Mei; Hens, Thorsten (Management Science, 2015)
We present results from a large-scale international survey on risk preferences conducted in 53 countries. In all countries, we find, on average, an attitude of risk aversion in gains and of risk seeking in losses. The degree of risk aversion shows significant cross-country differences. Moreover, risk attitudes in our sample depend not only on economic conditions but also on cultural factors, as measured by the Hofstede dimensions individualism and uncertainty avoidance. The data may also serve as an interesting starting point for further research on cultural differences in behavioral economics. Data, as supplemental material, are available at http://dx.doi.org/10.1287/mnsc.2013.1869 . This paper was accepted by Peter Wakker, decision analysis.